Reactive self-consumption strategy to suppress SiO2 phase transition-induced cracking - Lin Chen; Shu-Wen Li; Chang-Jiu Li; Qiang Zhang; Guan-Jun Yang (Journal of Advanced Ceramics)
The lifetime of Si bond coats in environmental barrier coatings (EBCs) is constrained by phase transition-induced cracking at the SiO₂ scale. In this study, reactive self-consumption and lattice solid solution strategies are employed to address this limitation via Si–Yb₄Al₂O₉ composite coatings. The formation of an Yb₂Si₂O₇ layer, through the consumption of the thermally grown SiO₂ scale and Yb₄Al₂O₉, reduces the SiO₂ thickness and significantly lowers the cracking driving force. Furthermore, the incorporation of Al into the SiO₂ lattice stabilizes high-temperature β-SiO₂, preventing phase transition-induced cracking. The proposed coating demonstrated an oxidation lifetime 20 times longer than that of pure Si at 1370 °C, highlighting its potential as an EBC bond coating.